Utilization of Organic Waste as Takakura Compost and Its Effect on The Growth of Chili Plants - Saputra, Yusva Dwi (citeus, 2024)
Garbage is still an environmental problem in Indonesia. One of the main causes of Indonesia's expanding waste problem is domestic garbage, of which 75 percent is organic waste. Although organic waste is easy to decompose, its accumulation can increase the greenhouse effect. Therefore, it is necessary to reduce organic waste. Takakura compost is one method of reducing organic waste that is not widely known. This experimental study was conducted to provide an overview of the Takakura composting method and its effect on the growth of chili plants. Composting uses an EM4 activator, and the variables observed in the composting process are described descriptively: temperature, pH, texture, odor, color, and humidity. The experimental plant variables were chili plant height in control and experimental groups, described descriptively and statistically tested with One-way ANOVA. The experimental group used in the compost produced followed the compost maturity parameters in SNI 19-7030-2004. The planting trial showed no effect between planting media added with compost and those that only used soil as growing media.